Analisis Pemahaman Integral Taktentu Berdasarkan Teori APOS (Action, Process, Object, Scheme) pada Mahasiswa Tadris Matematika (TMT) IAIN Tulungagung - Sholihah, Ummu; Mubarok, Dziki Ari (IAIN Ponorogo, 2016)
This research aims to describe the understanding ofmathematics Tadris students ofÂ IAIN TulungagungaboutÂ indefinite integral understanding of APOS theory. The subjects of research are six students. Each two haveÂ high, average, and low abilities. The result of the research indicated that the understanding ofmathematics Tadris (TMT) students ofÂ IAIN Tulungagung about indefinite integral understanding on actionaspect of APOS theory, high students achieve all of understanding indicators, for average students also achieveÂ all of understanding indicators, meanwhile for low students achieve one indicator of two indicators. On process aspect, high students achieve all of understanding indicators and average students achieve all of understanding indicators too. Meanwhile low students achieve one indicator of three indicators. On objectaspect,high students achieve all of understanding indicators and average students achieve one indicator of three understanding indicators. Meanwhile for low students do not achieve all of understanding indicators. On schemeaspect, high students achieve all of understanding indicators and for average students achieve two understanding indicators. Meanwhile for low students achieve only oneÂ indicatorsØØ§ÙÙØª ÙØ°Ù Ø§ÙÙ ÙØ§ÙØ© Ø¹Ø±Ø¶ ÙÙÙ Ø·ÙØ§Ø¨ ÙØ³Ù ØªØ¹ÙÙÙ Ø§ÙØ±ÙØ§Ø¶ÙØ§Øª ÙÙ Ø§ÙØ¬Ø§Ù Ø¹Ø© Ø§ÙØ¥Ø³ÙØ§Ù ÙØ© Ø§ÙØÙÙÙ ÙØ© ØªÙÙÙÙØ¬ Ø£ØºÙÙØ¬Ø Ø¹Ù Ø§ÙØªÙØ§Ù ÙØ§Øª Ø¥ÙÙ Ø£Ø¬Ù ØºÙØ± Ù Ø³Ù ÙÙ Ø¹ÙÙ Ø£Ø³Ø§Ø³ ÙØ¸Ø±ÙØ© Â APOS. ÙÙÙÙØµÙÙ Ø¥ÙÙ Ø§ÙØ£ÙØ¯Ø§ÙØ Ø§ØªÙØ¨Ø¹ ÙØ°Ø§ Ø§ÙØ¨ØØ« Ø§ÙÙ ÙÙØ¬ Ø§ÙÙÙÙÙØ Ø¨Ø¹Ø±Ø¶ ÙØªØ§Ø¦Ø¬ Ø§Ø³ØªÙØ¹Ø§Ø¨ Ø§ÙÙÙÙ Ø¹ÙÙ Ø£Ø³Ø§Ø³ ÙØ¸Ø±ÙØ© APOS. ÙÙ ØµØ§Ø¯Ø± Ø§ÙØ¨ÙØ§ÙØ§Øª ÙÙØ°Ø§ Ø§ÙØ¨ØØ« ÙÙ Ø³ØªØªØ© Ø·ÙØ§Ø¨: Ø·Ø§ÙØ¨Ø§Ù Ø°ÙÙÙØ§ÙØ ÙØ·Ø§ÙØ¨Ø§Ù Ù ØªÙØ³Ø·Ø§Ù ÙÙ Ø§ÙØ°ÙØ§Ø¡ ÙØ·Ø§ÙØ¨Ø§Ù Ø¶Ø¹ÙÙØ§Ù. Ø¯ÙØª ÙØªØ§Ø¦Ø¬ Ø§ÙØ¨ØØ« Ø¹ÙÙ Ø£Ù ÙÙÙ Ø·ÙØ§Ø¨ ØªØ¯Ø±ÙØ³ Ø§ÙØ±ÙØ§Ø¶ÙØ§Øª ÙÙ Ø§ÙØ¬Ø§Ù Ø¹Ø© Ø§ÙØ¥Ø³ÙØ§Ù ÙØ© Ø§ÙØÙÙÙ ÙØ© ØªÙÙÙÙØ¬ Ø£ØºÙÙØ¬ Ø¹ÙÂ Ø§ÙØªÙØ§Ù ÙØ§Øª Ø¥ÙÙ Ø£Ø¬Ù ØºÙØ± Ù Ø³Ù ÙÙ ÙÙ Ù Ø±ØÙØ© Ø§ÙØªØ·Ø¨ÙÙ ÙØ§Ù Ø§ÙØ·Ø§ÙØ¨Ø§Ù Ø§ÙØ°ÙÙØ§Ù ØªÙÙÙØ±Øª ÙÙÙÙ Ø§ Ø¬Ù ÙØ¹ Ù Ø¤Ø´Ø±Ø§Øª Ø§ÙÙÙÙ Ø ÙØªÙÙÙØ± Ø¬Ù ÙØ¹ Ù Ø¤Ø´ÙØ±Ø§Øª Ø§ÙÙÙÙ ÙØ°ÙÙ ÙÙ Ø§ÙØ·Ø§ÙØ¨ÙÙ Ø§ÙÙ ØªÙØ³Ø·ÙÙ ÙÙ Ø§ÙØ°ÙØ§Ø¡Ø Ø£Ù Ø§ ÙÙ Ø§ÙØ·Ø§ÙØ¨ÙÙ Ø§ÙØ¶Ø¹ÙÙÙÙ ÙØªÙÙÙØ±Øª ÙÙÙÙ Ø§ Ù Ø¤Ø´ÙØ±Ø© ÙØ§ØØ¯Ø© ÙÙØ·. ÙØ£Ù Ø§ ÙÙ Ù Ø±ØÙØ© Ø§ÙØ¹Ù ÙÙØ© ÙØ¥Ù Ø§ÙØ·Ø§ÙØ¨ÙÙ Ø§ÙØ°ÙÙÙÙÙ ØªÙÙÙØ±Øª ÙÙÙÙ Ø§ Ø¬Ù ÙØ¹ Ù Ø¤Ø´Ø±Ø§Øª Ø§ÙÙÙÙ Ø ÙÙÙ Ø§ÙØ·Ø§ÙØ¨ÙÙ Ø§ÙÙ ØªÙØ³Ø·ÙÙ Ø°ÙØ§Ø¡ ÙØªÙÙÙØ± ÙÙÙÙ Ø§ Ø¬Ù ÙØ¹ Ù Ø¤Ø´Ø±Ø§Øª Ø§ÙÙÙÙ ÙØ°ÙÙØ Ø£Ù Ø§ ÙÙ Ø§ÙØ·Ø§ÙØ¨ÙÙ Ø§ÙØ¶Ø¹ÙÙÙÙ ÙØªÙÙÙØ±Øª ÙÙÙÙ Ø§ Ù Ø¤Ø´Ø±Ø© ÙØ§ØØ¯Ø© ÙÙØ· Ù Ù Ø«ÙØ§Ø« Ù Ø¤Ø´Ø±Ø§Øª. ÙÙÙ Ù Ø±ØÙØ© Ø§ÙÙ ÙØ¶ÙØ¹Ø ÙØ¥Ù Ø§ÙØ·Ø§ÙØ¨ÙÙ Ø§ÙØ°ÙÙÙÙ ØªÙÙÙØ± ÙÙÙÙ Ø§ Ø¬Ù ÙØ¹ Ù Ø¤Ø´Ø±Ø§Øª Ø§ÙÙÙÙ Ø ÙØ§ÙØ·Ø§ÙØ¨Ø§Ù Ø§ÙÙ ØªÙØ³Ø·Ø§Ù ÙØªÙÙÙØ± ÙÙÙÙ Ø§ Ù Ø¤Ø´Ø±Ø© ÙØ§ØØ¯Ø© ÙÙØ· Ù Ù Ø«ÙØ§Ø« Ù Ø¤Ø´Ø±Ø§Øª Ø§ÙÙÙÙ Ø ÙØ£Ù Ø§ Ø§ÙØ·Ø§ÙØ¨Ø§Ù Ø§ÙØ¶Ø¹ÙÙØ§Ù ÙÙØ§ ØªØªÙÙÙØ± ÙÙÙÙ Ø§ Ø£ÙØ© Ù Ø¤Ø´Ø±Ø© Ù Ù Ø«ÙØ§Ø« Ù Ø¤Ø´Ø±Ø§Øª Ø§ÙÙÙÙ . ÙØ£Ù Ø§ ÙÙ Ù Ø±ØÙØ© Ø§ÙØªØ®Ø·ÙØ· ÙØ¥Ù Ø§ÙØ·Ø§ÙØ¨ÙÙ Ø§ÙØ°ÙÙÙÙ ØªÙÙÙØ±Øª ÙÙÙÙ Ø§ Ø¬Ù ÙØ¹ Ù Ø¤Ø´Ø±Ø§Øª Ø§ÙÙÙÙ Ø ÙÙÙ Ø§ÙØ·Ø§ÙØ¨ÙÙ Ø§ÙÙ ØªÙØ³Ø·ÙÙ ØªÙÙØ±Øª ÙÙÙÙ Ø§ Ù Ø¤Ø´Ø±ØªØ§Ù ÙÙØ·Ø ÙØ£Ù Ø§ ÙÙ Ø§ÙØ·Ø§ÙØ¨ÙÙ Ø§ÙØ¶Ø¹ÙÙÙÙ ÙØªÙÙÙØ±Øª ÙÙÙÙ Ø§ Ù Ø¤Ø´Ø±Ø© ÙØ§ØØ¯Ø© ÙÙØ·